Translator pen - Mohd Shukeri, Norashikin; Roslan, Adyputra Syah Iyman; Harun, Misbahulfalah; Hassim, Hasniza (Universiti Teknologi MARA, Kedah, 2019)
The machine translation actually gave us an idea and inspiration to create one of the product that also involve with translation which is translator pen. We named our product as “Honyakusha Pen”. Besides that, not only the machine translation that gave us an idea or inspiration but also our product inspired from Quran Pen Translator. We design the pen to be more sophisticated using a new trend of technology. Our pen is designed to make it easy for students to read and understand a variety of language not only in English or Bahasa. Our pen can translate all languages because we are using chip that contain system translations (SYSTRANS) and there’s no limitations. The next one of course when we already produce this pen, it’s actually requires a few steps or process in how to handle with our product or commonly known as how to use this pen. Our Honyakusha Pen will be put at the edge of the chairs in the library. It is because it will be easier for students or users to retrieve it rather than they have to be in a long queue just to get the pen. So it will save their time and energy. Basically the basic function of this pen is reads in text. So firstly, users have to move the pen over the text, and the text will be captured by the pen and at the same time an audio will be appear which is the system that we used can directly detect the text and produce with the voice. So users may use earphones. But actually it’s an option because of we have a screen that the text also will appear on the screen and depends on the users if they don’t want to used earphones they can only read the text on the screen. If they are auditory learners, they may prefer to use the earphones. This pen is basically can translate the text from various of languages and it is very easy to use which is you only have to simply slide over the word that you required translated and within less than a second the results is displayed.